Risk factors of early onset type 2 diabetes mellitus in young adults ≤ 40 years old (Universa Medicina, 2024)
BackgroundThe global prevalence of type 2 diabetes mellitus (T2DM) in adolescents and young adults is dramatically increasing. The aim of this study was to explore numerous risk factors for the occurrence of Pre-DM or T2DM in subjects aged ≤40 years.MethodsA cross-sectional study was conducted involving 100 subjects (50 subjects in the Pre-DM/T2DM group and 50 subjects in the Non Pre-DM/T2DM group). Main inclusion criteria: age ≤40 years, registered in our Diabetes and Endocrine Clinic. Data extracted included demographic, lifestyle, anthropometric, psychosocial, and family history data. Statistical analysis by binary logistic regression model. Results were considered significant at p